Comets and asteroids - Nardo, Don 1947-; Gale Group (San Diego, Calif. Lucent Books, 2004)
Discusses the history of comets and asteroids, how they are formed, where they are found, and what impact they made have on the future of the Earth.
Comets demystified, asteroids discovered -- How asteroids and comets formed -- Vital statistics of asteroids and comets -- Voyages to the comets and asteroids -- How humans will mine asteroids and comets -- When comets and asteroids strike earth.
Electronic reproduction.
Keywords: Comets -- Juvenile literature; Asteroids -- Juvenile literature; Electronic books